The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/00000542-200405000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cell-mediated Immunity and Increased Postoperative Infection Rate in Long-term Alcoholic Patients

Abstract: T helper cell-mediated immunity was significantly suppressed before surgery and possibly led to inadequate cytotoxic lymphocyte and whole blood cell response in long-term alcoholic patients after surgery. This altered cell-mediated immunity might have accounted for the increased infection rate in long-term alcoholic patients after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 70 publications
3
93
2
4
Order By: Relevance
“…Excessive alcohol consumption is known to have deleterious effects on the immune system (1)(2)(3)(4)(5). Chronic alcohol administration in experimental animal systems leads to a decrease in the absolute numbers of CD4 + T lymphocytes from the periphery and the spleen as well as a reduction in their immune function (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol consumption is known to have deleterious effects on the immune system (1)(2)(3)(4)(5). Chronic alcohol administration in experimental animal systems leads to a decrease in the absolute numbers of CD4 + T lymphocytes from the periphery and the spleen as well as a reduction in their immune function (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The altered cytokine production results in a balance that favors an antiinfl ammatory profi le when exposed to surgical stress. 82 Cytokine abnormalities have been linked to the development of nosocomial sepsis in surgical and trauma patients.…”
Section: Surgical Patientsmentioning
confidence: 99%
“…64,65,82,[92][93][94][95] Two highly innovative studies suggested that the use of sedatives and opioids may infl uence the stress response and immune function. 48,49 Spies et al 48 demonstrated that the use of opioids may result in modulation of the stress response and result in improved outcomes.…”
Section: Management Of Sedationmentioning
confidence: 99%
“…2 Furthermore, low interleukin-6/interleukin-10 (IL-6/IL-10) ratios have been associated with a significantly increased postoperative infection rate. 3 The immune response to tissue injury can be divided into innate and acquired responses.…”
Section: Spies M Kip a Lau Et Al Enhanced Hla-dr Expression Aftmentioning
confidence: 99%